Tourists’ perception of hotel frontlines’ questionable behaviors in Penang Island / Fairuz Abd Hakim, Norhamizan Hamir and Nor Azhar Mohd Taib - Abd Hakim, Fairuz; Hamir, Norhamizan; Mohd Taib, Nor Azhar (2011)
Previous scholars agreed that tourists’ satisfaction is the main objective in hotel business which reflects the service profit chain concept where satisfied employees will treat the customers fairly then lead to happy customers and satisfied customers will contribute to the organization profitability through repeat purchase and brand loyalty. However, the issues of questionable work behaviors always arise in hotel industry particularly in the three main departments. Questionable behaviors define as the behavior that not certainly right or wrong and thought to be important to at least that part of the market which makes return trips and also to the process of ‘word-of-mouth’ recommendations that visitors may engage in. Owing to the definition, it could be concluded that the effect of such behaviors is very bad since it involves the long-term profitability and growth of the hotel. This research was assessing on the tourists’ perception regarding questionable work behaviors by hotel frontline employees in all the three pillar-of-the- house departments which are front office, food and beverages, and also housekeeping. Not to forget, this research not only examining the tourists' perception but at the same time exploring the relationship between the variables of interest. Findings discovered that questionable work behaviors have a positive relationship with tourists' satisfaction.